Development and feasibility of inquiry-based articulate storyline interactive media on food chain materials for grade V elementary school students - Amienatul Raisyah; Sri Cacik (Edulab : Majalah Ilmiah Laboratorium Pendidikan, 2026)
Purpose - This study aims to develop and analyze the feasibility of inquiry-based interactive media utilizing Articulate Storyline on food chain materials for Grade V elementary school students. Design/methods/approach - This study employed a Research and Development (R&D) approach using the ADDIE model. The interactive learning media based on Articulate Storyline was developed based on a needs analysis and designed by integrating an inquiry-based learning approach. The feasibility of the product was evaluated through expert validation and subsequently analyzed using descriptive quantitative techniques in the form of percentage scores. Findings - The results showed that the developed media obtained feasibility scores of 96.9% from media experts, 96.9% from material experts, and 95.8% from language experts, all of which were categorized as highly feasible. These findings suggest that the developed media is feasible for use in Science and Social Studies (IPAS) learning because, both pedagogically and technically, it is capable of facilitating students' understanding of abstract food chain concepts through visualizations, simulations, inquiry activities, and interactive evaluations. Research implication/limitation - This study is limited to the product development and feasibility testing stages and, therefore, has not examined the effectiveness of the media in improving students' learning outcomes, conceptual understanding, learning motivation, or critical thinking skills. Originality/value - The novelty of this study lies in the integration of inquiry-based learning principles into Articulate Storyline-based learning media specifically developed for food chain materials. In addition to offering innovation in learning technology, this study provides a pedagogical contribution through a media design that combines multimedia learning principles with the inquiry process to support more meaningful IPAS learning in elementary schools.